Impact of profile resilience on energy confinement - Igitkhanov, Yu.; Janeschitz, G.; Sugihara, M. (Вопросы атомной науки и техники, 2000)
Multi-machine experimental observations indicate resilience in the temperature profiles at low pedestal temperatures, whereas at high pedestal temperatures the profile stiffness seems to disappear. The change of the profile behavior impacts the energy confinement, basically due to a strong non-linear dependence of the energy transport on the pedestal temperature together with different critical conditions for the onset of turbulence in the ions and electrons. This possible explanation for the different observations is based on the assumption that both ion and electron energy transport is governed by turbulence which sets in at a critical temperature gradient as well as on a significant energy equipartition between electrons and ions.